Nonlinear backstepping controller design for bridge‐type fault current limiter to enhance the transient performance of hybrid power systems. (12th September 2021) - Islam, Md. Rashidul; Upadhay, Arghya Das; Roy, Tushar Kanti; Hasan, Jakir; Mahmud, Md. Apel
Summary: A nonlinear backstepping control scheme is proposed in this work for a bridge type fault current limiter (BFCL) in a hybrid power system for enhancing its transient performance. The hybrid power system has the provision to supply AC loads connected to the main grid and local DC loads. The DC‐side of that system is coupled with AC‐side through a bidirectional converter having power exchange capability between both AC‐ and DC‐sides. The AC‐side is coupled with the main grid through transmission lines and the BFCL is placed on the transmission line, where the faults are considered, as the transmission line is the most vulnerable point. The dynamical model of the BFCL is used to design the nonlinear backstepping controller (BSC) where the control input is derived in a way that it can ensure as well as enhance the transient performance of that hybrid power system. Lyapunov stability theory is used to theoretically demonstrate the stability of the BFCL using the proposed BSC. Theoretical findings guarantee the system stability, and simulation studies clearly indicate the superiority of the proposed BSC based BFCL (BSC‐BFCL), both graphically and numerically over an existing nonlinear sliding mode controller (SMC) for the BFCL (SMC‐BFCL), for symmetrical and unsymmetrical fault scenarios (both temporary and permanent type). In addition, percentage overshoot and settling time analyses suggest the lesser deviation of system responses during transients from their ideal values and quicker stability, respectively. Moreover, the astonishing total harmonic distortion (THD) values with the proposed technique signify the excellency over its competitors in every aspect. Abstract : A nonlinear backstepping controller is designed in this paper for bridge‐type fault current limiter to augment the transient performance of a DFIG/SG/PV/PMSG based hybrid AC‐DC power system. This proposed technique provides almost seamless system responses even during various fault scenarios.